Microbial Surface Confined Growth Strategy for the Synthesis of Highly Loaded NiCoP Nanoparticles with Hollow Derived Carbon Shells for Sodium Ion Capture - Jianhua Yuan; Tianxiao Sun; Jinfeng Chen; Runhong Zhou; Jianglin Cao; Fei Yu; Liqing Li; Xiumin Zhong; Jie Ma (Advanced Science)
Abstract NiCoP is considered to be a very promising material for sodium ion (Na+) capturing, however, the volume expansion and poor cyclic stability of NiCoP during the storage limit its application. In response to these limitations, Finite element simulations are used to help in the rational design of the NiCoP structure. A novel microbial surface confined growth strategy is employed to synthesize highly loaded NiCoP nanoparticles (NiCoP NPs) supported on hollow derived carbon shells (NPC), constructing a stable composite structure known as NiCoP@NPC. The highly loaded and uniformly dispersed NiCoP NPs are anchored in‐situ and fully exposed, enabling enhanced electron and ion transport efficiency and thereby boosting pseudocapacitance. The NPC from yeast played a crucial role in mitigating the volume expansion of NiCoP NPs, thereby enhancing the structural stability of the electrode. Consequently, NiCoP@NPC demonstrated a high Na+ storage capacity of 59.70 ± 1.51 mg g−1 at 1.6 V and maintained good cycling stability, retaining over 73.3% of its capacity after 80 cycles at 1.6 V. Scanning transmission X‐ray microscopy (STXM) analysis confirmed the reversible conversion reaction mechanism and the robust structure of NiCoP@NPC before and after the reaction; Density function theory (DFT) and electrochemical quartz crystal microbalance (EQCM‐D) further confirmed that the structural design of NiCoP@NPC promoted electron transport, Na+ adsorption as well as improved cycling stability. This study is intended to provide a new idea for the in‐situ confined synthesis of metal phosphides electrodes with stable performance and structure.